The archives of the Royal Council of Indies: Origin, organization and use (XVI-XVIII centuries) - Gómez Gómez, Margarita (2022)
The present study aims to analyze the birth, organization and use that the Royal Council of the Indies made of the archives throughout the Old Regime. As the main institution of the government and administration of the new conquered territories, the Council of the Indies generated and received an immense amount of written documents that very soon became one of the main channels of communication and information of the monarchy aside and another from the Ocean. The study of the birth and use of archives in the Council and its evolution over time will allow us to better understand the conception and the value given in each era to documents as instruments of government, but also as means of representation and memory of the ruler.